2017
DOI: 10.15666/aeer/1503_477508
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Geochemistry Constraints on the Genesis of the NO.2 Porphyry Copper-Gold Deposit in the Xiongcun District, Gangdese Porphyry Copper Belt, Tibet, China

Abstract: Abstract. The Xiongcun district is located in the western segment of the Gangdese porphyry copper belt (GPCB). The No.2 deposit in the Xiongcun district hosts a measured and indicated resource of 1.34 Mt copper, 76.34 t gold, and 193.78 t silver. The copper-gold mineralization of the No.2 deposit is mainly hosted in the Early Jurassic quartz diorite porphyry which intruded volcano-sedimentary rocks of the Early Jurassic Xiongcun Formation. S and Pb isotopic compositions of the ore sulfides and Re contents of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Geochemical compositions of the Xietongmen ore‐bearing porphyries: (a) TAS diagram; (b) SiO 2 versus K 2 O diagram; (c) A/CNK versus A/NK. Literature data for the Xietongmen No.I and No.II ore‐bearing porphyries refer to Huang, Tang, Lang, Zhang, and Chen (), Qu et al (), Tafti (), and Yin et al ()…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geochemical compositions of the Xietongmen ore‐bearing porphyries: (a) TAS diagram; (b) SiO 2 versus K 2 O diagram; (c) A/CNK versus A/NK. Literature data for the Xietongmen No.I and No.II ore‐bearing porphyries refer to Huang, Tang, Lang, Zhang, and Chen (), Qu et al (), Tafti (), and Yin et al ()…”
Section: Resultsmentioning
confidence: 99%
“…I and No. II ore‐bearing porphyries refer to Huang et al (), Qu et al (), Tafti (), and Yin et al (). MORB, mid‐ocean ridge basalt; ORG, ocean ridge granite; Syn‐COLG, syn‐collision granite; VAG, volcanic arc granite; WPG, within‐plate granite…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the sandstones most likely formed in an oceanic island arc rather than a continental island arc. Similarly, the Jurassic igneous rocks in the Xiongcun porphyry copper–gold district were also interpreted to have been generated within an oceanic island-arc system (Tang et al 2015; Lang et al 2017; Ma et al 2017 b ; Yin et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, some studies have reported that the geological setting of the southern Lhasa subterrane was a continental island-arc setting during the Late Triassic–Jurassic period (e.g. Yang et al 2008; Zhu et al 2008; Ji et al 2009; Guo et al 2013; Meng et al 2016 a , b ; Wang et al 2016; Ma et al 2017 a ), whereas others have suggested that it was probably an oceanic island-arc setting (Aitchison, Ali & Davis, 2007; Kang et al 2014; Huang et al 2015; Tang et al 2015; Lang et al 2017; Ma et al 2017 b ; Ma, Yi & Xu, 2017; Yin et al 2017). This controversy limits our understanding of the tectonic evolution of the southern Lhasa subterrane.…”
Section: Introductionmentioning
confidence: 99%
“…The Gangdese belt is a key metallogenic region within the Qinghai-Tibet Plateau collisional orogenic belt, where both continental collision porphyry Cu-Mo and magmatic arc porphyry Cu-Au deposits have been discovered, with their formation considered to be closely related to adakites [2,7,15,16,21,[35][36][37][38]. In terms of the metallogenic time scale, typical large to giant porphyry deposits within the Gangdese belt mainly formed during the Cenozoic collisional orogenic stage.…”
Section: Introductionmentioning
confidence: 99%